Hubungan Perhatian dan Motivasi dari Orang Tua dengan Hasil Belajar Tahfidz Siswa MTsN 6 Pasaman Barat - Emilida Emilida; Endri Yenti; Januar Januar; Khairuddin Khairuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is motivated by the existence of obstacles in learning tahfidz, namely children's lack of interest in learning tahfidz, difficulty in memorizing and not fluently and this is influenced by factors of attention and motivation from parents which influence students' tahfidz learning outcomes.This research aims to see and test how big the relationship is between attention and motivation from parents and the tahfidz learning outcomes of MTsN 6 West Pasaman students. This research uses a quantitative approach with a correlation type, the selection of research subjects is carried out using random sumpling techniques. The data collection method was carried out using questionnaires and documentation of graders. Data analysis was carried out through the data processing stage using a tabulation table Liker scale, validation, Cronbach's Alpha reliability, normality test, linear regression test, multiple regression test, F test, T test and hypothesis test. The results of the research show that (1) The relationship between parental attention and the tahfidz learning outcomes of MTsN 6 West Pasaman students shows a correlation coefficient of 0.686 or 68,6% seen from the interpretation table in the range of 0.60 -0.78, which means that the relationship between variables X1 and Y has a high correlation.(2) Motivation from parents and its relationship with the tahfidz learning outcomes of MTsN 6 West Pasaman students shows that motivation from parents is 0.626 or 62,6% according to the value correlation interpretation value based on the range 0.60-0.78, namely variables X2 and Y have a strong correlation. (3) The relationship between attention and motivation from parents and the tahfidz learning outcomes of MTsN 6 West Pasaman students is 0.704 or 70,4%, which has a strong level of relationship, and seen from the change table, it is 0.00, less than 0.05, which infers attention and motivation from parents. together or simultaneously related to variable Y or students' tahfiz learning outcomes. The results of the determination test carried out showed attention and motivation from parents with students' tahfidz learning outcomes at MTsN 6 West Pasaman amounting to 49.5% while 50.5% was determined by other factors.